Analisis Efisiensi Reproduksi Domba Ekor Gemuk Di Kabupaten Lombok Timur - Rr. Agustien Suhardiani; Rina Andriati; Muhamad Ashari (Faculty of Animal Husbandry, University of Mataram, 2018)
This research was conducted in the enclave of livestock production Fat-Tailed Sheep (DEG) in the district of East Lombok for the purposes to know the reproduction efficiency level of the DEG covering digits are Anestrus postpartum (APP), numbers service per conception (S/C), Service period (SP), days open (DO), Lambing Interval (LI) and body weight of the age at puberty. The location determination is done by purposive sampling based on the management system. Sampling livestock was done randomly as many as 30 DEG (15 tails at each location have been determined). Observations began from giving birth parent DEG until back pregnant. To determine differences in levels of reproductive efficiency of sheep tail fat at different management system the dates were analyzed using a t-test. The management system was a significant effect (P <0.05) to the reproductive efficiency of sheep tail fat. Parent DEG reared semi-intensively experiencing an estrus postpartum estrus, Days Open, and Lambing interval is longer than the parent DEG reared intensively.